Pengembangan Skala Religiusitas untuk Subyek Muslim - Yulmaida Amir (Indonesian Journal for The Psychology of Religion, 2021)
Research on religiosity is numerous, but the scales for Muslim subjects are limited. The present study aims to develop a measure of religiosity with the dimensions of religious belief, religious practice or behavior, and also religious experience, based on Islamic teachings. The results from empirical research on 769 student respondents, and psychometric testing of measuring instruments obtained 13 items that are feasible and reliable to be used as a measure of religiosity. This measuring instrument is named the Muslim Religiosity Scale